Identification of potential drug candidates to combat COVID-19: a structural study using the main protease (mpro) of SARS-CoV-2. Issue 17 (22nd November 2021) - Sharma, Pradeep; Vijayan, Viswanathan; Pant, Pradeep; Sharma, Mohita; Vikram, Naval; Kaur, Punit; Singh, T. P.; Sharma, Sujata
Abstract: The recent outbreak of the SARS-CoV-2 virus leading to the disease COVID 19 has become a global pandemic that is spreading rapidly and has caused a global health emergency. Hence, there is an urgent need of the hour to discover effective drugs to control the pandemic caused by this virus. Under such conditions, it would be imperative to repurpose already known drugs which could be a quick and effective alternative to discovering new drugs. The main protease (Mpro) of SARS-COV-2 is an attractive drug target because of its essential role in the processing of the majority of the non-structural proteins which are translated from viral RNA. Herein, we report the high-throughput virtual screening and molecular docking studies to search for the best potential inhibitors against Mpro from FDA approved drugs available in the ZINC database as well as the natural compounds from the Specs database. Our studies have identified six potential inhibitors of Mpro enzyme, out of which four are commercially available FDA approved drugs (Cobicistat, Iopromide, Cangrelor, and Fortovase) and two are from Specs database of natural compounds (Hopeaphenol and Cyclosieversiodide-A). While Cobicistat and Fortovase are known as HIV drugs, Iopromide is a contrast agent and Cangrelor is an anti-platelet drug. Furthermore, molecular dynamic (MD) simulations using GROMACS were performed to calculate the stability of the top-ranked compounds in the active site of Mpro. After extensive computational studies, we propose that Cobicistat and Hopeaphenol show potential to be excellent drugs that can form the basis of treating COVID-19 disease. Communicated by Ramaswamy H. Sarma